Ulū al-albāb approach in sustaining absorptive capacity for innovative behavior among knowledge workers in Malaysia - Mhd. Sarif, Suhaimi; Ismail, Yusof (2019)
Innovation requires absorptive capacity to enable companies to create, maintain and sustain competitive advantage for superior performance. There is a need to sustain innovative behaviour among knowledge workers. Ulū Al-Albāb approach provides an ecosystem for community of practice and knowledge workers to create, share, store, and transfer. This paper aims to investigate the influence of Ulū Al-Albāb approach in sustaining absorptive capacity for innovative behaviour among knowledge workers in Malaysia. The research aims to explore factors that contribute to absorptive capacity for innovative behaviour in the existing practice. The research also asks in what ways of sustaining absorptive capacity and innovative behaviour through the Ulū Al-Albāb approach. The study used personal interview with knowledge workers in Malaysia's ICT sector. The interview questions are accompanied with procedures and protocol that has been validated by experts and practitioners. Likewise, the interview results are analysed with procedures and validated by independent reviewers. The results of the study showed that Ulū Al-Albāb Approach has been practiced in the community of practice (COP) but without sustainable eco-system. Enhancement of Ulū Al-Albāb Approach occurs not only at individual and group, but also happens at organizational level. The study recommends Ulū Al-Albāb Approach to incorporate into education and training systems.